Lung cancer tumor immune microenvironment: analyzing immune escape mechanisms and exploring emerging therapeutic targets - Wang, Zhen; Guo, Honglei; Song, Yanqi; Wang, Aidi; Yan, Yuting; Ma, Lin; Liu, Baoshan (Frontiers in Immunology, 2025)
Lung cancer is the most common malignant tumor in the world. Presently, there are still problems, including a high recurrence rate, resistance, and serious toxic side effects, even if conventional treatments like chemotherapy, radiotherapy, and targeted therapy have somewhat improved patient survival. Even though immune checkpoint inhibitors that target programmed cell death-1/programmed cell death ligand 1 have fundamentally altered the therapeutic paradigm, the core mechanism is strongly linked to tumor immune escape, and some patients continue to have poor response rates or treatment resistance. The mechanisms of immune escape in the immunological microenvironment of lung cancer, involving metabolic reprogramming, overexpression of immune checkpoint molecules, and abnormalities in antigen presentation, are systematically summarized in this review. The article also sums up new therapeutic targets and promising clinical trials. The goal is to provide a solid theoretical foundation for further research into the immune escape mechanism, the creation of new immunotherapeutic targets, and personalized therapeutic strategies.